Surviving the city - Spillett, Tasha, 1988- (Highwater Press, 2018)
Two indigenous teens, Miikwan and Dez, find strength in their friendship with one another. But when her grandmother becomes sick, Dez runs away to avoid being sent to a group home. Miikwan is devastated by the loss of her friend and is determined to find her.